2011
DOI: 10.1029/2011jd016698
|View full text |Cite
|
Sign up to set email alerts
|

Lunar skylight polarization signal polluted by urban lighting

Abstract: [1] On clear moonlit nights, a band of highly polarized light stretches across the sky at a 90 degree angle from the moon, and it was recently demonstrated that nocturnal organisms are able to navigate based on it. Urban skyglow is believed to be almost unpolarized, and is therefore expected to dilute this unique partially linearly polarized signal. We found that urban skyglow has a greater than expected degree of linear polarization (p = 8.6 AE 0.3%), and confirmed that its presence diminishes the natural lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 27 publications
4
44
1
2
Order By: Relevance
“…The increase in the magnitude of sky glow by artificial lights in cities is also likely to affect these behaviours and, in addition, may interfere with the navigation of many species which use celestial patterns of light to orientate themselves in the night-time environment4344. For example, artificial light has been shown to disrupt the orientation and therefore migration direction of birds45, and concerns have been raised about the interference of artificial light pollution with celestial polarized sky light patterns28 which many insects4647484950 and birds5152 use to navigate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the magnitude of sky glow by artificial lights in cities is also likely to affect these behaviours and, in addition, may interfere with the navigation of many species which use celestial patterns of light to orientate themselves in the night-time environment4344. For example, artificial light has been shown to disrupt the orientation and therefore migration direction of birds45, and concerns have been raised about the interference of artificial light pollution with celestial polarized sky light patterns28 which many insects4647484950 and birds5152 use to navigate.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of direct artificial light include navigational disorientation of birds1415, turtles1617 and invertebrates1819, the displacement and concentration of selected foraging habitat in bats2021 and birds22, the extension of foraging times in birds222324, and changes to the composition of invertebrate communities25. Added to this, the potential effects of sky glow include artificially increasing the amount of ambient light and time available for foraging2627, interfering with celestial light patterns used in navigation28, and the disruption of temporal activity patterns linked to daily, monthly and annual lunar rhythms in sky brightness29303132. Understanding how sky glow alters natural regimes of sky brightness is therefore fundamental to investigating its environmental impacts.…”
mentioning
confidence: 99%
“…Although the azimuthal angle has been ignored in almost all past skyglow simulations, it has been suggested that azimuthal variations due to the screening of light not directed along street canyons could be responsible for the generation of linearly polarized skyglow [10]. These histograms were filled with the number of times that a radiometer performed an observatino in the given direction, as well as the observed radiance (in digital numbers).…”
Section: Methodsmentioning
confidence: 99%
“…This system is able to measure the upwards emission from zenith to an angle of 70 o , for any given azimuthal direction. Testing whether the upward emitted light is azimuthally symmetric is of interest, because it could explain the polarization of skyglow observed by Kyba et al (2011). Azimuthally symmetric emission is generally assumed by skyglow models (e.g.…”
Section: Overviewmentioning
confidence: 99%